Microservices-Driven Automation in Full-Stack Development: Bridging Efficiency and Innovation With FSMicroGenerator - Samira Khalfaoui; Hafida Khalfaoui; Abdellah Azmani (IEEE Access)
The development of modern web applications presents major challenges due to increasingly complex architectures, scalability requirements, and the need to reduce time to market. These challenges are exacerbated by the shortage of talent, making the implementation of modern architectures more difficult for many companies. In response, this article presents FSMicroGenerator, an innovative code generation tool based on a low-code approach, which exploits UML class diagrams and templates to generate multilingual, full-stack web applications based on a microservices architecture. FSMicroGenerator automates the entire process of creating IT solutions, from development to deployment, reducing technical barriers and technical debt, and enabling teams to focus on business innovation while ensuring compliance with industry standards and best practices. By facilitating the adoption of DevSecOps practices, it improves collaboration between the development and operations teams, ensuring that security is integrated at every stage of the development process. This enables continuous management of the application lifecycle, faster and more reliable releases, and proactive identification and mitigation of security vulnerabilities. FSMicroGenerator also stands out for its ability to create a catalog of ready-to-use functional blocks, enabling their reuse and integration into other solutions. In addition, it offers a secure ecosystem, protecting companies’ assets against the risks of data exposure and leakage thanks to a robust architecture and integrated security mechanisms. As part of our open innovation approach, we plan to make FSMicroGenerator open source, to broaden its adoption and enable the community to contribute to its continuous improvement.